Defying an ominous sign: complete neurological recovery after bilateral fixed dilated pupils in hypercapnic respiratory failure - Sody A. Naimer (European Journal of Case Reports in Internal Medicine, 2026)
Introduction: Bilateral fixed dilated pupils (BFDP) have traditionally been regarded as an ominous sign indicating severe brainstem dysfunction and poor neurological prognosis, often prompting discussions regarding withdrawal of life-sustaining treatment. However, pupillary abnormalities can also result from reversible metabolic derangements, including severe hypercapnia, profound acidosis, and hypoxia. Current guidelines emphasize that pupillary assessment should occur after correction of confounding factors such as hypoxemia, hypotension, and metabolic disturbances. Case description: A 66-year-old man with a history of ischemic stroke six months prior presented with prolonged generalized seizures, vomiting, and progressive loss of consciousness. On arrival to the Emergency Department, he was unconscious with bilaterally dilated, unreactive pupils. Venous blood gas analysis revealed severe respiratory acidosis with pH 6.96 and pCO2 102 mmHg. Despite intubation and mechanical ventilation, he developed profound desaturation followed by cardiac arrest with ventricular tachycardia requiring cardioversion. A brain computed tomography scan showed no new intracranial pathology. Chest radiography demonstrated massive bilateral aspiration pneumonia. Following aggressive resuscitation, mechanical ventilation, broad-spectrum antibiotics, and supportive care, his respiratory parameters and acidosis gradually improved. As his respiratory status normalized, his pupils became constricted and reactive to light. The patient was successfully weaned from mechanical ventilation and regained full consciousness with complete restoration of cognitive function. Conclusion: Bilateral fixed dilated pupils in severe hypercapnic respiratory failure may be a transient and fully reversible phenomenon when driven by metabolic derangements rather than structural brain injury. Timely resuscitation and deferral of definitive prognosis until confounding metabolic factors have been corrected is essential to avoid premature withdrawal of life-sustaining treatment.